Isolation and characterization of melanin from palm fiber. Issue 5 (4th July 2019) - Xiao, Xiuyun; Zhang, Jinju; Cheng, Lu; Liu, Xingxing; Jiang, Ying; Zhang, Tonghua
ABSTRACT: Melanin pigments derived from palm fiber were isolated via acid/ethanol extraction, acid hydrolysis, organic solvent (e.g., ethanol, ethyl acetate, and acetone) treatment, and repeated precipitation. Ultraviolet-visible and infrared spectra analyses showed that the melanin pigments derived from palm fiber were similar to typical melanin. The stability of palm fiber pigments in oxidants, reducing agents, metal ions, temperature, and light was investigated. Results revealed that the stability of palm fiber pigments was good in the oxidant, hydrogen peroxide, but relatively poor in the reducing agent, sodium sulfite. The derived melanin pigments were significantly affected by Fe 3+, Al 3+, Cu 2+, and Zn 2+, but only slightly affected by Na +, Mg 2+, and Ca 2+ . In addition, palm fiber pigments exhibited poor thermal endurance at high temperatures and under room lighting. A study on antioxidant activity showed that palm fiber pigments exhibited strong scavenging capability against free radicals. Moreover, its removal capability was enhanced by increasing pigments concentration. Its scavenging capability was arranged from weak to strong as follows: 1, 1-diphenyl-2-picrylhydrazyl < O 2 − < OH.